Recent developments and achievements in biocybernetics and biomedical engineering : proceedings of the 20th Polish Conference on Biocybernetics and Biomedical Engineering, Kraków, Poland, September 20-22, 2017 /: proceedings of the 20th Polish Conference on Biocybernetics and Biomedical Engineering, Kraków, Poland, September 20-22, 2017. (2017) - Unknown
No abstract available